TEMPORAL AND AXIAL VARIATIONS FOR PRIMARY NUTRIENT CONCENTRATIONS IN LEAVES OF LITCHI - RAGINI KUMARI,; PRABHAKAR MAHAPATRA,,; KUMARI NISHA,,; RAJEEV KUMAR,; RAJENDRA PRATAP SINGH, (The Bioscan, 2015)
An experiment was conducted in an established orchard (since, 1979) planted with cultivars Shahi and China at ICAR Research Complex for Eastern Region, Ranchi Centre (ICAR) to study temporal and axial variations for primary nutrient concentrations in leaves of Litchi as well as their interrelationship with crop productivity with the main objective to find out time of sampling and pair of leaves suitable for leaf tissue analysis in litchi for predicting nutrient deficiency in litchi and recommending most suitable time of sampling. Periodic collection of leaf samples from established orchard was done during the 2006-07; analysis of leaf samples for primary nutrients (N, P and K) in plant (leaf) part was carried out. Leaf concentration of N, P and K varied from 1.08 to 1.20, 0.081 to 0.109 and 0.690 to 0.786 percent, respectively. However, mean leaf nutrient concentration was 1.14, 0.095 and 0.738 percent for N, P and K, respectively. Highest concentration of N was observed for the 2nd pair of leaves where as for P and K was 1st pair of leaves. Significant relationship between yield and concentration were observed in 2nd and 4th pair of leaves. Sampling of 2nd and 4th pair of leaves of litchi during February to April or September to November was most suitable time in predicting.